(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Brucellosis is a zoonotic infection transmitted from animals to humans by the ingestion of infected food products, direct contact with an infected animal or inhalation of aerosols. The socio-economic significance of the problem of brucellosis is the course of the disease with the development of chronic forms and disability. Therefore, early detection, treatment and follow-up observation of those who have recovered from the disease are of great epidemiological importance.